Vertical innovation, foreign direct investment, and asymmetric imitation: A welfare analysis of intellectual property protection. (Southern Economic Journal, 2021)
The paper examines the intertemporal welfare effects of strengthening intellectual property (IP) protection in the South using a North–South quality‐ladder model, where South‐bound foreign direct investment (FDI) serves as a bridge to transfer production from the North to the South. Modeling features include costly FDI, asymmetric productivity between multinational and Southern firms, and asymmetric imitation risks confronting multinational and Northern firms. In contrast to the literature, the paper shows that strengthening Southern IP protection cannot serve the Southern interest, although it can promote vertical innovation and South‐bound FDI. The North may reap a welfare gain, but it depends on whether Northern households are a dominant equity owner of Northern and multinational firms or whether the IP‐determined imitation risks are not too much biased towards multinational firms.